FRI0311 Is ultrasonography of salivary gland a useful tool in sjögren syndrome? a systematic review. (23rd January 2014) - Jousse-Joulin, S.; Bowman, S.; Milic, V.; Jonsson, M. V.; Plagou, A.; Theander, E.; Luciano, N.; Pascale, R.; Baldini, C.; Bootsma, H.; Tzoufias, A. G.; Bombardieri, S.; et al.
Abstract : Objectives: Ultrasonography of salivary glands is a new test to diagnose primary Sjögren syndrome (pSS) 1 . We assess the diagnostic value of ultrasonographic abnormalities of salivary gland in pSS using a systematic review of literature Methods: PUBMED and EMBASE databases were searched. The following association of MeSh terms was used: "SALIVARY GLANDS" AND "SJOGREN'S SYNDROME" AND "ULTRASONOGRAPHY". All publications between January 1988 and January 2013, in English language and concerning patients addressed for suspected or established pSS were considered. Sensitivity and specificity of US were collected or calculated when possible. Data were extracted from the articles meeting the inclusion criteria, focused on the US definition of scoring systems used, and metric properties studied. The type and number of glands tested, study design, and quality of the studies were assessed. Results: 167 publications were identified with EMBASE and 182 with PUBMED. 30 articles were selected. The number of pSS included patients varied from 20 to 150. In most of the studies (19/30), sensitivity and specificity to detect US abnormalities were performed in established pSS. Sensitivity ranged from 44.2 % to 86 % and specificity from 73 % to 100%. Specificity was > 90 % in 12 studies.US examination was performed for diagnosis, in suspected pSS in only 5 studies 1 -5, the sensitivity ranged from 58.8% to 87% and specificity from 90% to 98.7%. The parotid and submandibular glands were the most commonly studied. The scoring system is heterogeneous using 5 differents scoring systems. The echostructure abnormalities in B mode were relatively homogeneous but few studies concerned the assessment of the vascularisation. In one study, the sensitivity and the sprecificity of the US technique increased with the addition of the color Doppler. The reliability was done in 10/30 studies and only for interobserver acquisition (most often between 2 sonographers) with a kappa varying from 0.8 to 0.95. Most of the studies were performed in a single center. Conclusions: This systematic review shows that very few studies are available to estimate the diagnostic value of US-pSS for suspected pSS. US in B mode had a high specificity but a high heterogeneity concerning the definition of abnormalities. The data concerning the use of Doppler are very scarce. Reliability of this technique is poorly investigated. Effort should be made to validate and standardized US in pSS. References: Cornec D, Jousse-Joulin S, Pers JO et al. Arthritis Rheum. 2013 Jan;65(1):216-25. Takagi Y, Kimura Y, Nakamura H et al Ann Rheum Dis. 2010 Jul;69(7):1321-4. Milic VD, Petrovic RR, Boricic IV et al. J Rheumatol. 2009 Jul;36(7):1495-500. Shimizu M, Okamura K, Yoshiura K et al. Oral Surg Oral Med Oral Pathol Oral Radiol Endod. 2008 Oct;106(4):587-94. Hocevar A, Rainer S, Rozman B et al. Eur J Radiol. 2007 Sep;63(3):379-83 Disclosure of Interest : None Declared